Challenges of Agri-Start-ups in Post-Harvest Cold Storage Technologies - Kumar, Alok; Ganesha, T. B.; Mishra, B.P.; Venkatesan, P.; Kumar, Sanjiv; Meena, P C; Prakash, Satya; Gupta, B. K. (Indian Journal of Extension Education, 2021)
Agri-start-ups are developing new products through a value chain, supply chain solutions, packaging, processing systems, infrastructure, warehousing, logistics, protection of foodstuffs, communications, e-commerce, delivery and retail models. The study aims to documentthe challenges of Agri-startups working in post-harvest and storage parameters of fruits and vegetables. To get the insight, primary and secondary survey was carried out and data was used to provide suggestionsto capture the customer and market.The data indicated that different units required different temperature range to store a different kind of commodity in their cold storage unit. 86.15% of units were using the backup generators. 53.84% of units were getting the commodities directly from farmers, 30.76% from traders, 9.24% from both and 6.15% from others.50.76% of units were desired to get low electricity bill and10.76 % of units were desired to come out of usage of generator whereas32.3 % of units were willing to get both i.e. low electricity bill and without dependency on generator and 6.15 % of units were willing to reduce other costs like operation cost, maintenance cost etc.70.76 % of cold storage units having a cooling tower.